Impaired Esophageal Mucosal Integrity May Play a Causative Role in Patients With Nongastroesophageal Reflux Disease–Related Noncardiac Chest Pain. Issue 51 (December 2015) - Min, Yang Won; Choi, Kyu; Pyo, Jeung Hui; Son, Hee Jung; Rhee, Poong-Lyul
Abstract : Abstract: Baseline impedance (BI) measurement can be used to evaluate the status of the esophageal mucosa integrity. We hypothesized that impaired esophageal mucosal integrity may play a causative role in patients with nongastroesophageal reflux disease (non-GERD)–related noncardiac chest pain (NCCP). This retrospective study analyzed 24-hour multichannel intraluminal impedance-pH testing data from 77 patients with NCCP and 5 healthy volunteers. BI was calculated at 3 cm (distal esophagus) and 17 cm (proximal esophagus) above the lower esophageal sphincter. GERD was defined by the presence of pathologic acid exposure or reflux esophagitis. Among the 77 patients with NCCP, 16 (20.8%) were classified into the GERD-related NCCP group and 61 (79.2%) into the non-GERD-related NCCP group. BI (median, interquartile range) of the non-GERD-related NCCP group was lower than the control group at the proximal esophagus (2507 Ω, 2156–3217 vs 3855 Ω, 3238–4182, P  = 0.001) but was similar at the distal esophagus. The GERD-related NCCP group showed lower BI than the control group at both the distal and proximal esophagus (2024 Ω, 1619–2308 vs 3203 Ω, 2366–3774, P  = 0.007 and 2272 Ω, 1896–2908 vs 3855 Ω, 3238–4182, P  = 0.003, respectively). At the distal esophagus, BI was lower in the GERD-related NCCP group than the non-GERD-related NCCP group ( P  = 0.002), whereas it did not differ between the 2 groups at the proximal esophagus. In conclusion, the mucosal integrity is impaired at the proximal esophagus in patients with non-GERD-related NCCP, which might be the pathogenic mechanism of NCCP.